Efficacy of Pregabalin with Methylcobalamin in Neuropathic Pain: A study in the Nepalese Population of Eastern Region - Gupta, Prem Kumar; Roy, R K; Jha, Ranjib Kumar; Paudel, Mahendra; Dewasy, Bijoylakshmi; Gupta, Prashant (Journal of Nobel Medical College, 2024)
Background: Neuropathic pain is a severe condition that is challenging to treat. The objective of this study was to determine the efficacy of a fixed-dose combination of sustained-release pregabalin and methylcobalamin in reducing neuropathic pain in Nepalese patients.Materials and Methods: This was a prospective, hospital based, observational study. Patients received fixed dose combination of 75 mg sustained-release pregabalin combined with 1500 mcg immediate release methylcobalamin. Data was collected at prefixed interval for pain reduction and associated comorbidities. Pain intensity was measured on a ten-point visual analog scale and sleep quality was measured by Sleep Quality Scale. Data was analysed   using appropriate statistical methods.Results: Out of the total patients, 52% belonged to the age group 39-59 years, with females more than males. Age and gender difference were statistically significant with neuropathic pain. The study also revealed that radiculopathy and diabetic neuropathy were significantly associated with specific age groups. Patients in severe and distressful pain in day 1 have significantly improved to mild (70%) and tolerable (24%) pain by day 14. The mean VAS score showed an overall reduction of 58.75% over 14 days. The comorbidities observed with neuropathy, were diabetes mellitus (42%), hypertension (22%), alcoholism (18%), and smokers (6%). By day 14, 85% and 11% patients reported to have good and excellent sleep quality, respectively, compared to the poor and fair sleep quality assessed on day 1 and day 7.Conclusion: There was significant improvement in pain and sleep quality with the use of 75 mg pregabalin and 1500 mcg methylcobalamin in patients with neuropathic pain.